Language Style Approach to Teaching Poetry in ESL Classroom - Kuswardani, Rahayu; Nur Abida, Fithriyah inda; Fahri, Fahri; Zuhri, Fauris (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2022)
The purpose of this study is to describe the method of using language style in poetry learning in the EFL classroom. Some of the methods used are focusing on the word choice, sentence structure, and figurative language of the selected poem. This research uses descriptive qualitative method. Data collection techniques are observation and documentation with conversation observation technique and writing technique. This study was conducted on 5th semester students majoring English education program at State University of Surabaya.The data of this research is a collection of poetry by Robert Frost. The data analysis technique uses the Miles and Huberman interactive model, namely, data reduction, data presentation, and verification. The results of this study found that the effective approach of teaching language style in poetry begins with a discussion of vocabulary in poetry, going on to a review of sentence structure and coherence, and finally continuing on to rhetoric and figurative language.Through this method of instruction, information is gradually transferred to students, who gain a better understanding of how to interpret poetry.